A case study on the influence of sorption inhomogeneities on the migration of contaminants - Lührmann, Ludger; Fein, Eckhard; Knabner, Peter (Environmental Sciences (B3110), 1998)
A two-dimensional numerical test case study was performed in order to investigate the influence of sorption inhomogeneities on the migration behaviour of contaminants. The sorption processes are modelled with a nonlinear kinetic-Freundlich reaction. Thereby a kinetic approach of first order is supposed. In a first test case homogeneous sorption parameters are used, and in a second case the transport path is divided into regions of low and high sorption. For the latter the numerical solution using the TRAPIC code requires a finer discretization in the region of the sorption inhomogeneities. The nonlinearities caused by the kinetic-Freundlich reaction are resolved using Newton's method. Besides the well known retardation of the contaminants caused by sorption processes the simulations yield the following results: The distribution of the concentration of the sorbed contaminants is discontinuous in the region of the sorption inhomogeneities. The nonlinear behaviour of the kinetic-Freundlich reaction counteracts the spreading effects of the contaminant caused by the diffusive and dispersive transpor